The making of a legitimate standard. (August 2022) - Hayes, Jan; Maslen, Sarah; Merad, Myriam
Highlights: Addresses social aspects of standard formation and what makes standards effective. Case study research of the update to a pipeline engineering standard. Input and output legitimacy in the eyes of users impacts compliance. Local content is important as is involvement of regulators. Abstract: Standards are a core part of risk regulation, acting as one of the key resources for technical professionals and their companies in the design and long-term management of hazardous infrastructure. Yet they lurk in the background, in so far as safety scientists rarely attend to what makes a particular standard effective. This paper contributes to the literature by focusing on the social aspects of standard formation and use, taking as our case a recent update to one part of AS 2885, the Australian Standard for pipeline engineering. Working with the ideas of 'input' and 'output' legitimacy in the eyes of end users, we address justification of the national standard, committee membership and the interests it reflects, and views about standard effectiveness. We identify high levels of input legitimacy for the standard due to its institutional links and high technical expertise of subcommittee members. The effectiveness of the standard to date confers output legitimacy. Input and output legitimacy, together, underlie standard compliance. The case suggests that compliance with safety standards more broadly might be supported by a higher profile for standards writers themselves. The link between industry culture and standards is emphasised as is the value of involving regulators in standard development.